The Changing Roles of Education and Ability in Wage Determination - Castex, Gonzalo; Kogan Dechter, Evgenia (Journal of Labor Economics, 2014)
This study examines changes in returns to formal education and cognitive skills over the past 20 years using the 1979 and 1997 waves of the National Longitudinal Survey of Youth. We show that cognitive skills had a 30%–50% larger effect on wages in the 1980s than in the 2000s. Returns to education were higher in the 2000s. These developments are not explained by changing distributions of workers’ observable characteristics or by changing labor market structure. We show that the decline in returns to ability can be attributed to differences in the growth rate of technology between the 1980s and 2000s.